MARKETING COMMUNICATION STRATEGY OF HALAL TOURISM AROUND GUS DUR’S CEMETERY IN JOMBANG - Afifatur Rohimah; Mohammad Insan Romadhan (INJECT (Interdisciplinary Journal of Communication), 2019)
This article aims to develop an appropriate strategy for halal tourism at the complex of Gus Dur’s cemetery. The aim of the study is to find out an appropriate marketing communication strategy that can be applied for halal tourism particularly in religious tourism complex, around Gus Dur’s cemetery. This study used descriptive qualitative method through a mapping approach in finding the data. The finding of the study is that the implementation of an appropriate marketing communication strategy of halal tourism around Gus Dur’s cemetery should consider several aspects including advertisement role, sales promotion, event enhancement, maximizing social relationships, social publicity, direct marketing with digital utilization, and growing good tourist image with the role of word of mouth. The marketing communication strategy that will be developed should refer to the concept of halal tourism; the so called Muslim-friendly environment. Throughout this marketing communication strategy, this will maximize the existence of religious tourism around Gus Dur’s cemetery both for local and international tourists.